Framing papal communication in the central Middle Ages. Issue 3 (27th May 2018) - Althoff, Gerd; Fonnesberg-Schmidt, Iben; Kynan-Wilson, William
ABSTRACT: This essay examines the production and consumption of papal communication in the central Middle Ages. It outlines the development of the papacy, which formed the historical and political framework for papal communication, and discusses the processes, themes and meanings behind various types of communication relating to the papacy in Latin Christendom principally between the years 1100 and 1300. Particular emphasis is placed upon the plurality of responses to papal communication and on the relationship between papal communication and authority, and papal self-identity and perceptions. The essay introduces seven diverse and interdisciplinary articles in a special issue of the Journal of Medieval History on the papacy and communication in the central Middle Ages.